PENEGAKAN HUKUM OLEH PETUGAS SYAHBANDAR PELABUHAN TARAKAN DALAM RANGKA KESELAMATAN PELAYARAN - Syafruddin Syafruddin; Syamsul Bahri (Universitas Borneo Tarakan, 2022)
AbstractThe aim of the study was to analyze the implementation of the law enforcement authority of the Tarakan Harbor Master in the context of shipping safety and the philosophy of the function of the Tarakan Harbor Master's authority in the context of law enforcement for shipping safety. Based on the legal issues studied, this research is directed at the peculiarities of jurisprudence which are normative in nature, so the type of this thesis research is normative legal research, namely research that examines issues regarding the harbor master of Tarakan Port in the framework of law enforcement for shipping safety. The results of the study show that the application of law enforcement authority for Class III Tarakan Port Syahbandar in the context of shipping safety, is divided into 2 (two), namely law enforcement that is implemented in a preventive and repressive manner. Preventively, namely law enforcement in the context of preventing acts against shipping laws, including: Supervising ships during the Covid-19 pandemic, supervising and monitoring ships that will sail; conducting sea patrols; make an appeal for the installation of passenger seat numbers; and do socialization. As for repressive law enforcement, its application includes: detaining captains who do not have sailing approval and confiscating ship equipment that does not meet shipping standards. Philosophically, the function of the authority of the harbor syahbandar in the framework of law enforcement for shipping safety is to reestablish the professionalism of the syahbandar as law enforcer in order to ensure maritime safety and security. That is, the essence of the function of this authority is to ensure the specific roles and duties of the harbor master, including the Class III Tarakan Port Master in law enforcement in the territorial waters of Indonesia. Keywords: Law Enforcement, Syahbandar, Class III Port of Tarakan